(untitled) (Historia, 2021)
With each succeeding publication on Christian missions in Southern Africa, some of the existing problems relating to this evocative subject are worse compounded. Traditional mythology continues to dominate -albeit in different forms -and superstructure is erected on shaky foundations, leading the unwary historian ever further from reality, especially when a doctrine or a cause is involved (and African history is so susceptible to both). Some of the current difficulties attending the study of Christian missions in Caffraria seem to have been generated by an inadequate perception of the physical nature of the mission station, the activities which took place there, and their relationships with Caffraria itself and the Cape Colony. Only when all this has been ascertained with reasonable accuracy can the historian move on. A lack of attention to these basic considerations sometimes leads to wrong inferences and conclusions.